Filosofía de la calidad y servicio al usuario en la Dirección Provincial MIDUVI-Los Ríos - Flores Elinan, Bruce Reinaldo (2017)
The Provincial Direction MIDUVI (Ministry of Urban Development and Housing) Ríos, is located in Av. Benetazo and Primera transversal, the same one that exercises legal representation, as a regional representation of the Ministry of Urban Development and Housing, since June 14, 1994, carrying out functions of urban development and environmental sanitation. At present, it develops planned programs like: bonds for construction of new housing, improvement, emergency and bonuses ¨Muela Espejo¨, to facilitate the conditions that make it possible for families with lower incomes to access to decent housing, or to improve the precarious housing they possess¨ (Ministry of Urban Development and Housing [MIDUVI], 2017).